The Effect of Promotion and Price on Purchase Decisions with Brand Image as a Mediating Variable: Evidence from Selalu Teh Consumers in East Kalimantan - Muhammad Fikri; Anton Hindardjo (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
This study aims to analyze the influence of promotion and price on purchasing decisions with brand image as a mediating variable on consumers of Selalu Teh PT. Foodinesia products in Kutai Kartanegara Regency. This study uses a quantitative method with Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis techniques. The results show that promotion and price have a positive and significant effect on brand image. Brand image is proven to have a positive and significant influence on purchasing decisions and mediates the influence of promotion and price on purchasing decisions. However, the direct effect of promotion on purchasing decisions is proven to be insignificant, while price has a positive effect although lower than brand image. These findings confirm that brand image is a key factor that strengthens consumer purchasing decisions. Therefore, companies need to strengthen brand image through more creative promotional strategies and competitive pricing. Academically, this study contributes as a reference for further research by adding other relevant variables to enrich the purchasing decision model.